A Novel Bionic Hand based on SMA Driven - Zhaoyang Huang (Jixie chuandong)
By using independent design method， the control module， figure module and thermal module of bionic hand are designed separately， the integration bionic hand is fabricated and can realization separation and assemble quickly. By using the Shape memory alloy（SMA）wire as actuator， the cam structure of displacement amplifier is designed， which can increase the output displacement of SMA in the driving process. Using Matlab， the simulation of kinematics and motion space is conducted， the bionic hand prototype is fabricated through 3D printing， which is 410 g. The response capability of bionic hand in different temperature environment and temperature protection for SMA are improved by temperature feedback， and grasping manipulation test for everyday objects is verified. Results show the novel bionic hand possesses the ability of grasping larger and heavier objects， and convenient disassembly and assembly， simple control， and stable grasping， which realizes the design of high integration.